The Effect Of Non Performance Loan (Npl) And Loan Deposit Ratio (Ldr) On Return On Asset (Roa) In Pt. Bank Rakyat Indonesia (Persero), Tbk - Agung Rahmat Ilahi; Karona Cahya Susena; Wagini Wagini (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
The purpose of this study was to determine the effect of Non Performance Loans (NPL) and Loan Deposit Ratio (LDR) on Return on Assets (ROA) at PT. Bank Rakyat Indonesia (Persero), Tbk. The sample in this study is the financial statements at PT. Bank Rakyat Indonesia (Persero), Tbk for the period 2010 to 2019 The data collection method uses the documentation method. The data analysis used is multiple linear regression, coefficient From the calculation of the multiple linear regression equation, it can be seen that the results of the regression test: Y = 14.944– 1.072 X1 - 0.099X2. The coefficient of determination obtained is 0.846. This means that X1 (Non Performance Loan (NPL)) and X2 (Loan Deposit Ratio (LDR)) have an effect on Return on Assets (ROA) (Y) by 84.6% while the rest (100% - 84.6% = 15.4%) is influenced by other variables not examined in this study. The results of the t test show that there is a significant effect between NPL and LDR on Return on Assets (ROA) (Y) at PT. Bank Rakyat Indonesia (Persero), Tbk partially or separately The results of the F test show that there is a significant influence between NPL and LDR on Return on Assets (ROA) (Y) at PT. Bank Rakyat Indonesia (Persero), Tbk simultaneously or collectively.of determination and hypothesis testing.